Penerapan Building Information Modelling 4D pada Perencanaan Jadwal Proyek Rehabilitasi Gedung Kantor BWS Kalimantan II Palangka Raya - Maryam; Waluyo, Rudi; Gawei, Apria Brita Pandohop (Jurnal Civil Engineering Study, 2025)
The increase in building construction requires the application of more effective and efficient methods to achieve optimal quality, time, and cost standards. One approach that has been widely developed in answering these challenges is Building Information Modeling. The rehabilitation project of the Kalimantan II River Basin Office Building still uses conventional planning without integrating BIM technology. This shows a gap between the potential of BIM and practice in the field, especially due to a lack of understanding of the technology. This study aims to determine the 3D structural model, determine the project schedule planning, and apply 4D BIM to the planning of the structural work schedule for the rehabilitation project for the Kalimantan II River Basin Office Building in Palangka Raya City. This research is a case study. The research was conducted at the Kalimantan II River Basin Office Building in Palangka Raya City along Jl. Tjilik Riwut Km 3.5. Implemented for 5 months, from September to February 2025. The research data are detailed engineering design, time schedule and technical specifications. The data analysis technique uses the building information modeling method. The results of the study showed that there was a 3D model of the building structure with a concrete quantity of 465.83 m³ and reinforcement of 56,364.86 kg. The implementation of 4D BIM with Autodesk Naviswork in schedule planning resulted in a total duration of structural work of 175 days, and produced a scheduling simulation that was integrated between the model and the implementation time. This integration has been proven to provide significant efficiency because it is able to reduce the correction or revision time that is common in conventional methods, while increasing accuracy, transparency, and coordination between parties involved in the construction project.